2008
DOI: 10.1007/s00468-008-0269-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of root architecture and root loss through trenching on the anchorage of tropical urban trees (Eugenia grandis Wight)

Abstract: International audienceEugenia grandis (Wight) is grown in urban environments throughout Malaysia and root systems are often damaged through trenching for the laying down of roads and utilities. We investigated the effect of root cutting through trenching on the biomechanics of mature E. grandis. The force necessary to winch trees 0.2 m from the vertical was measured. Trenches were then dug at different distances (1.5, 1.0 and 0.5 m) from the trunk on the tension side of groups of trees. Each tree was winched s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 44 publications
0
25
0
1
Order By: Relevance
“…For instance, several authors report that the stability of a tree may fail as soon as inclination reaches close to 20° (Cucchi and Bert, 2003;Stokes, 1999), whereas other authors observed that the yield of trees may be associated with rotation values at the base of only 2-5° (Coutts, 1983;Jonsson et al, 2006;Lundström et al, 2007). Very flexible trees have been even reported to return to their upright position after having been deflected to angles >40° (Crook and Ennos, 1998;Ghani et al, 2009). Root deformation was, moreover, found to be about half in young tree trunks and roughly one-third in older trees (Stokes, 1999).…”
Section: Uncertainties and Model Limitationsmentioning
confidence: 93%
“…For instance, several authors report that the stability of a tree may fail as soon as inclination reaches close to 20° (Cucchi and Bert, 2003;Stokes, 1999), whereas other authors observed that the yield of trees may be associated with rotation values at the base of only 2-5° (Coutts, 1983;Jonsson et al, 2006;Lundström et al, 2007). Very flexible trees have been even reported to return to their upright position after having been deflected to angles >40° (Crook and Ennos, 1998;Ghani et al, 2009). Root deformation was, moreover, found to be about half in young tree trunks and roughly one-third in older trees (Stokes, 1999).…”
Section: Uncertainties and Model Limitationsmentioning
confidence: 93%
“…pine [8,[16][17][18], spruce [8,[19][20][21]; and birch [8]. Only a few had implemented the test on tropical trees, such as Samanea saman [22][23][24][25], Aglaia and Nephelium [26], Vitellaria paradoxa [27], Eugenia grandis [28] whereas to the best of our knowledge, none had tried it on Paraserianthes falcataria, a tree native to Indonesia, which is locally known as sengon. The analysis on sengon is crucial, especially considering its massive population in some urban areas in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…이러한 실험적 연 구를 통하여 수목의 전도는 뿌리의 길이, 직경, 표면적, 최 대 뿌리발달깊이 등에 따라 서로 다른 형태를 보여주고 있다 (Bischetti et al, 2005;Dupuy et al, 2005;Stokes et al, 2005). 또한, DBH, 수고, 수간부의 중량 및 체적과 같은 수목의 지상부 특성 (Moore, 2000;Achim et al, 2005;Ghani et al, 2009;Urata et al, 2012)과 토양점착 력, 토양 단위중량, 토심 등과 같은 토양 특성 (Bischetti et al, 2005;Dupuy et al, 2005;Khuder et al, 2007) (Nicoll et al, 1995;Stokes et al, 1997). 하지만, 수목의 뿌리는 고유의 유전적인 특성과 토양 및 지하수 등 환경 특성에 따라 공 간적으로 생장 및 분포가 다른 형태로 나타나므로, 뿌리 의 형태적 특성을 일반화하기가 쉽지 않다.…”
unclassified